Perception of the population of Morro do Pilar (MG) on the implantation of a mining enterprise in the municipal (Research, Society and Development, 2018)
Mining plays an important role in the economy of a country, and is fundamental for obtaining the necessary raw materials for people's daily lives. However, this activity has negative impacts on the environment, such as the landscape degradation, deforestation, water contamination and air pollution. In this way, this research had the objective of analyzing the population perception of Morro do Pilar (MG), about the socio-environmental and economic impacts that can be triggered by the implantation of a mining enterprise in the city from a questionnaire applied to 340 residents. Thus, concerning to the positive impacts, the participants of this research highlighted the growth of the municipality and the generation of employment for the population. Considering the negative socio-environmental and economic impacts were mentioned pollution, environmental destruction, increase of people who are not from the region and violence in the city. In this sense, the importance of public participation in public hearings is emphasized, since it is through this action that information is obtained regarding the mining activity development and the measures that will be adopted to minimize and/or eliminate the negative effects of this upon the environment and society.